Youth employment in Sierra Leone : sustainable livelihood opportunities in a post-conflict setting - Peeters, Pia (World Bank e-Library., 2009)
Creating job opportunities for a large and growing number of young people is a key development challenge for the government of Sierra Leone. Analyzing the supply and demand sides of the labor market, this book asseses the challenges and options for improving sustainable livelihood opportunities for youth in post-conflict Sierra Leone.